Dichloridotetrakis(1H-1,2,4-triazole-κN (4))copper(II) - Vidmar, Maja (International Union of Crystallography, 2012)
The central Cu(II) atom of the molecular title complex, [CuCl(2)(C(2)H(3)N(3))(4)], is situated on a site with symmetry 2.22. It is six-coordinated in an elongated octahedral geometry, with the equatorial plane defined by four N atoms of four 1,2,4-triazole ligands and the axial positions occupied by two Cl atoms situated on a twofold axis. The molecules are connected via N—H⋯Cl hydrogen bonds and the crystal consists of two interpenetrating three-dimensional hydrogen-bonded frameworks.